Burden of Caregivers of Patients with Chronic Diseases in Primary Health Care: A Cross-Sectional Study in Greece - Eleni N. Albani; Aikaterini Toska; Constantinos Togas; Spyridon Rigatos; Viktor Vus; Evangelos C. Fradelos; Anastasios Tzenalis; Maria Saridi (MDPI AG, 2024)
Background: In the world of elderly people and people with chronic diseases, caregivers give a solution to caring at home. This study aimed to evaluate the burden of caregivers of patients with chronic diseases in primary health care and identify possible demographic and other determinants of it. Methods: This was a cross-sectional study with a convenience sample, which was conducted in two health centers. The sample comprised 291 caregivers who visited the aforementioned health centers in Patra, Greece. A composite questionnaire was utilized: the first part included demographic data and care-related information and the second included the Zarit Burden Interview and the Depression, Anxiety, and Stress Scale-21 (DASS-21). Results: The highest mean score in the DASS was recorded in the depression subscale and the lowest in the stress subscale. Concerning the Zarit Burden Interview, the highest mean score was recorded in the personal strain subscale and the lowest in the management of care subscale. The highest correlation was recorded between role strain and anxiety and the lowest was between management of care and stress. Similarly, the total score in the Zarit Burden Interview correlated significantly (in a positive direction) with depression, anxiety, and stress. Conclusions: Most of the caregivers of patients with chronic diseases in primary health care experienced a moderate to severe burden (especially in the dimension of personal strain) and moderate depression. The experienced burden was positively associated with depression, anxiety, and stress. There were significant differences in the caregivers' burden according to several demographic and care-related characteristics.